Ticari bankalarda aktif pasif yönetimi ve ölçeklerine göre seçilen bankalarda camels analizi uygulaması - Kütükoğlu, Kerem (My University, 2004)
MİLLİ EĞİTİME BAĞLI MESLEK OKULLARINDA GÖREV YAPAN ÖĞRETMENLERİN İŞ TATMİNİ Bu araştırmada Milli Eğitime bağlı meslek eğitimi veren okullarda görev yapan öğretmenlerin iş tatmin durumlarını belirlemek amaçlanmıştır. Bu doğrultuda meslek liselerinde görev yapan öğretmenlerin iş tatminlerinin cinsiyet, medeni durum, yaş, mesleki deneyim, meslek tercihi, ikinci gelir ve aylık net gelir değişkenlerinden nasıl etkilendiği araştırılmıştır. Araştırma 4 bölümden oluşmuştur. Birinci bölümde araştırma konusu ile ilgili giriş ifadeleri yer almaktadır. Bu bölümde problemin durumu ortaya konmuştur. İkinci bölümde konunun teorik kısmı verilmiştir. Üçüncü bölümde tez çalışmaları, izlenilen yöntem ve teknikler ile bulgular yer almaktadır. Dördüncü bölümde sonuçlar, tartışma ve öneriler yer almaktadır. Bu araştırma için Minnesota Tatmin Ölçeği ve Kişisel Bilgiler Formu olmak üzere iki kısımdan oluşan bir ölçek kullanılmış, araştırmaya İstanbul'da 12 ayrı okuldan 311 öğretmen katılmıştır. Araştırmanın istatistik analizlerinde SPSS kullanılmış, ikili gruplar arasında anlamlı farklılıkları tespit etmek için t-testi, çoklu gruplar için varyans analizi yapılmıştır. Araştırmada ayrıca konunun teorik altyapısına, iş tatmini konusunda yapılmış araştırmalara, konu ile ilişkili kavramlara, iş tatmininin ve iş tatminsizliğinin etkilerine ve motivasyon teorilerine de yer verilmiştir. Bu çalışmada mesleki eğitim kurumlarında çalışan öğretmenlerin, bağlı bulundukları kurumlardan ne derece memnun oldukları, nelerden tatminsizlik duydukları, sosyal kimlikleri ile iş tatminleri arasındaki ilişki tespit edilmeye çalışılmıştır. Eğitim yöneticilerine, bu sonuçları dikkate alarak çalışanları için daha uygun çalışma ortamları sağlayabilmeleri, onları, bağlı bulundukları kurumun hedeflerini ve değerlerini kabullenen, motivasyonu ve performansı yüksek çalışanlar haline getirebilmeleri için bilimsel kaynak sunma düşüncesi araştırmanın diğer bir amacı olmuştur. Temmuz , 2004 Bahtiyar BALCİ

JOB SATISFACTION OF TEACHERS EMPLOYED AT OCCUPATIONAL STATE SCHOOLS In this research, our purpose is to determine the level of job satisfaction of the teachers working at occupational high schools controlled by National Education Ministry. For this reason, how the variables as sex, marital status, age, working experience, whether the job chosen on self decision or not and monthly net income affect the level of occupational satisfaction of these teachers working at occupational high schools is searched. The research comprises 4 parts. In the first part, a foreword is given on the subject of the research. In this part, the nature of the problem is explained. In the second part, the theoretical explanation of the subject is stated. In the third part, thesis studies, the methods and the techniques which were followed and findings are given. In the fourth part, results, arguments and suggestions are stated. For this research, a scale composed of two parts, namely Minnesota Satisfaction Questionnaire and Personal Information Form, was used and 311 teachers from 12 schools in Istanbul participated the research. In the statistical analysis of the research, SPSS program was used and for determining the meaningful differences between binary groups, t- test; for multiple groups, variance analysis was applied. Besides that, in the research, the theoretical basis of the subject, researches made on occupational satisfaction, concepts about the subject, the effects of job satisfaction or dissatisfaction and motivational theories are also given. In this research, it was attempted to determine the amount of satisfaction that the teachers get from the schools they work at; from what they feel dissatisfaction; the relation between their social identities and occupational satisfaction. Another aim of the research is that, by considering the results reached, educational directors can prepare more convenient working medium for their staff and make them understand the aims and values of the institutions they work for, and make them highly motivated and therefore having a better performance. July, 2004 Bahtiyar BALCİ Abstract When banking systems are evaluated, their level of globalization and their parallelism to the accepted internatianal standarts and principles are more important than the size of the systems. It is expected that the importance of risk management techiniques and analysis of them especially in internal control systems will increase in accordance with the rapid change in the banking techniques in the world. There fore, in this piece of work the asset liability management which is a deducation is studied broadly. The management of profit risk which is caused by either balance or off balance and the asset liability management which is essential to minimize the probable liquidation problems by analysing cash flow, are researched thorougly. Forward, future, swap and option, which are the precaution techniques against probable profit ratio, liquidation and currency risk are explained with mathematical operations related to asset liability, coherently and avoiding repetition. İn the conclusion of the work CAMELS analysis which is one of the analyses used in asset liabilty is also explained.
Keywords: Banka ve bankacılık; Ekonomi; Finansman ekonomisi; Ticari Bankalar; Ticari bankalar (Takas bank)